MENINGKATKAN AREA PEMASARAN UMKM PISAU DESA HADIPOLO DENGAN PENJUALAN ONLINE DI MASA PANDEMI COVID 19 - Arif Setiawan; Supriyono Supriyono; Pratomo Setiaji (Muria Jurnal Layanan Masyarakat, 2021)
The knife craft industry is one of the creative industries in Kudus Regency, especially in the village of Hadipolo Kudus. The problem faced by knife craft SMEs in the village of Hadipolo is the lack of access to marketing, sales only around Central Java through metal sales agents, HR capabilities are still minimal regarding technology. PPPUD team Muria Kudus University is working with the SMEs knife UD. Hasil Logam, designed an online sales web system to market products. The method used in this PPPUD activity is the expansion of marketing through online sales web and the UMKM YouTube channel knife, strengthening the internet infrastructure at UMKM, so that the market segment can reach the international level. The output targets of this PPPUD activity are expected to be able to: (1) increase UMKM assets, namely increase in production facilities (2) improve the quality of products produced, namely knives with plastic handles (3) expand marketing area.